Faktor-Faktor Yang Mempengaruhi Minat Siswa Dalam Mengikuti Ekstrakurikuler Futsal Di SD Negeri 032 Tilil Bandung - Galuh Alam, - (2021)
Extracurricular is a program outside school hours, in the form of student activities, optimization of related lessons, channeling talents and interests. Basically, elementary school children participate in extracurricular activities based only on pleasure or imitating friends without knowing the direction and purpose. For this reason, when students do an activity or activity it must be based on motivation and interest. This study aims to determine the factors that influence student interest in participating in futsal extracurricular activities at SD Negeri 032 Tilil, Bandung. This research design is a descriptive quantitative research with survey methods and data collection techniques using a questionnaire. The population in this study were all students who participated in futsal extracurricular activities at SDN 032 Tilil Bandung with a total sample of 60 students. The sampling technique in this study used total sampling. The technique of collecting data using a questionnaire and observation. The data analysis technique used in this research is descriptive with a quantitative approach. The results showed that the factors that influenced students' interest in joining futsal extracurricular activities at SD Negeri 032 Tilil Kota Bandung, that internal factors contributed 51.10% in internal factors divided into 3 indicators, namely Motivation / Ideals of 12.37. %, Attention is 14.43%, and pleasure is 24.30%. External factors contributed 48.9%. External factors are divided into 3 indicators, namely Teachers / Trainers at 14.46%, Parents at 12.74%, and Peers at 21.70%. From these results, it can be concluded that internal factors are factors that can increase student interest in joining futsal extracurricular activities.